Reconsidering Peer Influences on Delinquency: Do Less Proximate Contacts Matter? - Payne, Danielle C. (Journal of quantitative criminology, 2007)
Much research on adolescent delinquency pivots on the notion of peer influence. The peer effect that is typically employed emphasizes the transmission of behaviors and attitudes between adolescents who are directly linked. In this paper, we argue that to rely solely on those direct social ties to capture peer influence oversimplifies the realities of adolescent society. We use data from the National Longitudinal Study of Adolescent Health to show that indirect peer relations can exercise independent influences on adolescent delinquency. Adolescents actively draw on the examples of friends of friends, and even more distal peers, as they develop their repertoires of action and identity. We argue, however, that this behavior actually reflects adolescents’ ongoing struggle to impress their closest friends and to preserve their social circle. Indeed, the extent to which adolescents are willing to model the behavior of indirect contacts seems to decline as that behavior becomes more dissimilar from that of their close friends. Our findings dovetail with an account of the adolescent as a rational actor who struggles for social acceptance in a complex peer environment which offers conflicting behavioral models.